TATA KELOLA BUMN DAN PERTUMBUHAN EKONOMI MENURUT KLASTER LAPANGAN USAHA PERUSAHAAN NEGARA DI INDONESIA - Purnama, Agustinus Febi Dwi; Priyono, Anhar Fauzan; Remi, Sutyastie Soemitro (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study analyzes the effect of good corporate governance and government capital support in SOEs on financial performance and economic growth according to business groups. State enterprises were grouped into 13 business groups based on the Central Statistics Agency for 2011-2019. Technical data analysis of this research panel uses the Fixed Effect Model (FEM), and Random Effect Model (REM). The results show that corporate governance has a positive effect on the financial performance of SOEs in the Information and Communication sector, as well as the Real Estate group. However, government support has a significant effect on reducing the financial performance of state companies engaged in the Construction sector; Procurement of Electricity and Gas; Manufacturing Industry; Agriculture, Forestry, and Fisheries. Nevertheless, in general, state enterprises still contribute to increasing economic growth.